Quantitative Structure Activity Relationship Study on the Inhibitory Activity of Antitumor Benzothiazole Derivatives Against MCF-7 Breast Cancer Cell Line - K. Sharma, Brij; Yashwant (Asian Journal of Chemistry, 2011)
The MCF-7 breast cancer cell line inhibitory activity of benzothiazole derivatives has been quantitatively analyzed in terms of Dragon descriptors using CP-MLR. The analysis has provided a rational approach for the development of new benzothiazole derivatives as MCF-7 breast cancer cell line inhibitors. The descriptors identified in CP-MLR analysis have highlighted the role of atomic properties in respective lag of 2D-autocorrelations (MATS5p) and modified burden eigenvalues (BELe3, BELe6, BEHm3 and BELp2), maximal electrotopological positive variation (MAXDP), information content index of 2nd order neighborhood symmetry (IC2) and the 9th order Galvez topological charge (GGI9) to explain the MCF-7 breast cancer cell line inhibitory actions of benzothiazole derivatives. Thus, the descriptors identified for rationalizing the activity give avenues to modulate the structure to a desirable biological end point.